Design of Flexible Pavement Thickness Using the MDP 2024 Method (Case Study: Perintis Road, Palangka Raya City) - Wahyu Hardio; Ina Elvina; Salonten Salonten (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose. This research aims to design the thickness of flexible pavement on Perintis Road, Palangka Raya City, by applying the 2024 Pavement Design Manual (MDP 2024). The study emphasizes the need for reliable road infrastructure that can accommodate increasing traffic volumes and ensure durability, cost-effectiveness, and safety. Materials and methods. The data used in this study include the California Bearing Ratio (CBR) values obtained from field testing with a Dynamic Cone Penetrometer (DCP) and the Average Daily Traffic (ADT). Field surveys were conducted along the designated road segment to collect both traffic and soil strength data. Results. The field test results show that the segment’s CBR value is 7.006%, while the ADT is 516,000 passenger car units (pcu) per day. Based on the analysis using MDP 2024, the required flexible pavement thickness is 315 mm. This design consists of a surface layer of 65 mm (30 mm HRS-WC and 35 mm HRS-Base) and a subbase layer of 250 mm. Conclusions. The findings of this research are expected to serve as a reference for road infrastructure planning in Palangka Raya and other regions. The recommended design ensures technical feasibility, cost efficiency, safety, and long-term sustainability.